Question and answer
multiply (s+f)(s^2 - sf +f^2)
f^3 + s^3 is the answer. (s+f)(s^2 - sf +f^2) = f^3 + s^3
Expert answered|migzptz|Points 5430|
Question
Asked 3/20/2012 12:48:15 PM
0 Answers/Comments
This answer has been confirmed as correct and helpful.
s
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
solve for v.... 6/v=9/v-1/2
Weegy: The answer is v = 4. :) User: solve for b.... b^2 - 6b - 7=0 (More)
Question
Expert Answered
Updated 9/20/2014 10:57:20 PM
2 Answers/Comments
6/v=9/v-1/2
6/v - 9/v = -1/2
-3/v = -1/2
v = -3/( -1/2)
v= -3 *(-2)
v = 6
Added 9/20/2014 10:56:18 PM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [9/20/2014 11:00:45 PM]
b^2 - 6b - 7=0
(b - 7)(b + 1) = 0
b = 7 or b = -1.
Added 9/20/2014 10:57:20 PM
multiply... (4x+4)(6x^2 +8x+3)
Weegy: a. Factor as: (x - 3)(x + 1)^3 = 0 zeros are at x = 3 and x = -1 y ' = 4x^3 - 12x - 8 4(x - 2)(x + 1)^2 zeros at x = 2 and x = -1 - - - - - - - - - - - - - - - - - - - - b. y " = 12x^2 - 12 y "(2) = 36 which is positive, [ so x = 2 is a minimum point y "(-1) = 0, an inflection point - - - - - - - - - - - - - - - - - - - - c. f(x) decreases from [-8, 2] and increases from [2, +8] - - - - - - - - - - - - - - - - - - - - d. f(x) is negative for x = [-1, 3] and positive for all other real values ] (More)
Question
Expert Answered
Updated 3/21/2012 11:26:01 AM
3 Answers/Comments
(4x+4)(6x^2 +8x+3) = 24x^3 + 56x^2 + 44x + 12
Added 3/20/2012 10:42:09 AM
This answer has been confirmed as correct and helpful.
Unflagged by andrewpallarca [7/7/2014 7:25:01 PM], Confirmed by andrewpallarca [7/7/2014 7:25:03 PM]
multiply (r+1/5)(r+1/4)
Weegy: r^2 + 9r/20 + 1/20 (More)
Question
Expert Answered
Asked 3/20/2012 1:17:17 PM
0 Answers/Comments
factor completely... 4x^8 - 12x^7 + 24x^6
Weegy: 4x^8 - 12x^7 + 24x^6 = 4x^6 (x^2 - 3x + 6) (More)
Question
Expert Answered
Updated 7/11/2014 12:10:08 AM
0 Answers/Comments
multiply... (-2z)^2 (4z^6)^2
Weegy: (-2z)^2 (4z^6)^2 = 64z^14 (More)
Question
Expert Answered
Asked 3/20/2012 1:58:32 PM
0 Answers/Comments
33,665,624
questions answered
GET
Answers.
GET THE APP.
weegy*
*
Get answers from Weegy and a team of really smart live experts.
S
R
L
P
Points 287 [Total 2706] Ratings 1 Comments 277 Invitations 0 Offline
S
L
P
Points 276 [Total 2095] Ratings 1 Comments 266 Invitations 0 Offline
S
L
Points 210 [Total 1135] Ratings 0 Comments 210 Invitations 0 Offline
S
L
P
P
L
P
Points 150 [Total 6191] Ratings 2 Comments 130 Invitations 0 Offline
S
L
R
P
P
R
Points 137 [Total 3871] Ratings 0 Comments 137 Invitations 0 Offline
S
L
P
Points 128 [Total 2086] Ratings 1 Comments 118 Invitations 0 Offline
S
L
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
Points 126 [Total 3578] Ratings 11 Comments 16 Invitations 0 Online
S
L
Points 63 [Total 188] Ratings 3 Comments 33 Invitations 0 Offline
S
L
R
P
Points 58 [Total 2867] Ratings 0 Comments 58 Invitations 0 Offline
S
Points 50 [Total 50] Ratings 4 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.